2020
DOI: 10.1111/ppa.13152
|View full text |Cite
|
Sign up to set email alerts
|

Heterodera schachtii infection affects nitrogen metabolism in Arabidopsis thaliana

Abstract: Nitrogen metabolism is important for physiological processes during normal growth and development, as well as plant defence responses. Second‐stage juveniles of the cyst nematode Heterodera schachtii penetrate into the root and initiate permanent feeding sites called syncytia, from which they draw all necessary nutrients. To unravel whether the cyst nematode infestation changes nitrogen metabolism, the enzymatic activity and gene expression of nitrate (NIA) and nitrite (NIR) reductases and glutamate dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…It was shown that MPKs, including soybean homologs of A. thaliana MPK3 and MPK6 described above, had a defensive role during the G. max response to H. glycines infection. Interestingly, in addition to the argumentation presented above, another face of the NO-MPKs interaction should be considered, especially taking into account the results presented earlier by our team in the article on the metabolism of nitrogen in H. schachtii-infected A. thaliana plants [23]. Siddique et al [20] showed elevated H 2 O 2 production in A. thaliana roots as a result of the H. schachtii infestation.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…It was shown that MPKs, including soybean homologs of A. thaliana MPK3 and MPK6 described above, had a defensive role during the G. max response to H. glycines infection. Interestingly, in addition to the argumentation presented above, another face of the NO-MPKs interaction should be considered, especially taking into account the results presented earlier by our team in the article on the metabolism of nitrogen in H. schachtii-infected A. thaliana plants [23]. Siddique et al [20] showed elevated H 2 O 2 production in A. thaliana roots as a result of the H. schachtii infestation.…”
Section: Discussionmentioning
confidence: 82%
“…Melillo et al [21] found a swift NO presence at 12 h after M. incognita infection in tomato roots, whereas Zhou et al [22] pointed to enhanced transcript levels of NO biosynthetic (nitrate reductase) and signaling (S-nitrosoglutathione reductase) genes at 7 days after infection. Therefore, on the basis of the above described data and our recently published results presenting significant alterations in the activity of nitrate and nitrite reductases and nitrate/nitrite amounts in A. thaliana plants infected with H. schachtii [23], it would be supposed that the changes in nitrogen metabolism induced by cyst nematode infection may coexist with altered RNS metabolism in infected plants. Thus, the aim of this research was to study the effect of H. schachtii infection on RNS metabolism in A. thaliana roots.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Our previous results showed that changes in plant nitrogen metabolism took place during cyst nematode infection (Labudda et al 2020a). Arginase (ARG), nitrogen metabolism-linked enzyme, was another enzyme that was analysed in these studies.…”
Section: Discussionmentioning
confidence: 99%